2018
DOI: 10.1007/s11266-018-0035-6
|View full text |Cite
|
Sign up to set email alerts
|

From Fellowship to Stewardship? Explaining Extra-Role Behavior of Volunteer Firefighters

Abstract: We present a research model of extra-role behavior, integrating the literature on public service motivation (PSM) with stewardship theory. We propose that the extent to which volunteers perform activities that go beyond role prescription depends on the individual's PSM. Our research model is further grounded in the notion that a stewardship-oriented organizational culture serves as a means to enhance the effect of PSM on extra-role behavior. We empirically test this research model in a sample of 475 Austrian a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 128 publications
(170 reference statements)
0
11
0
Order By: Relevance
“…The perceived relationship with the immediate supervisor is the greatest determinant of job satisfaction and intention to remain (Rice and Fallon, 2011). Perceived organizational support influences the willingness to make an extra effort on behalf of the organization (Schmidthuber and Hilgers, 2019; Lee and Olshfski, 2002b). Perceptions of recognition, fairness of procedures and supervisor support are related to increased satisfaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The perceived relationship with the immediate supervisor is the greatest determinant of job satisfaction and intention to remain (Rice and Fallon, 2011). Perceived organizational support influences the willingness to make an extra effort on behalf of the organization (Schmidthuber and Hilgers, 2019; Lee and Olshfski, 2002b). Perceptions of recognition, fairness of procedures and supervisor support are related to increased satisfaction.…”
Section: Resultsmentioning
confidence: 99%
“…Firefighters with high levels of public service motivation perform more than is required and employees with altruistic beliefs also spend more time performing this extra work. Motivating work design, commitment and perceived organizational support directly influence the level of this extra effort behavior (Schmidthuber and Hilgers, 2019). Both younger and older generations of non-career firefighters are highly oriented towards serving the community, but younger people are also more driven to attain personal success (Francis and Jones, 2012).…”
Section: Retentionfactors That Influence the Decision To Remainmentioning
confidence: 99%
“…Moreover, according to the norm of reciprocity (Settoon et al , 1996), volunteers who perceive a higher level of POS (i.e. a beneficial action by the organization) are likely to return a benefit as a way to respond to a beneficial action (Schmidthuber and Hilgers, 2019). Thus, it is possible that volunteers may regard future volunteering as a reciprocal way of responding to a beneficial action made by the host organization (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, a positive organizational climate not only encourages job performance and a positive organization-employee relationship, but also improves employee job satisfaction that is capable of triggering employees’ volunteer participation motivation ( Gheitani et al, 2018 ; Saks, 2022 ). Group cohesion and socialization experiences formed by organizational climate can affect employees’ willingness to increase their extra-role behavior ( Schmidthuber and Hilgers, 2019 ), such as doing more volunteer work or engaging themselves more in civic activities good for their organization ( Soelton et al, 2020 ).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Studies have shown that by enhancing group identification and cohesion, an organization’s leader can trigger employees’ OCB by creating a positive organizational climate ( Kao, 2017 ; Liao et al, 2022 ). Organizations can also use various formal and informal systems to create a good atmosphere and shape employees’ positive thinking and motivation for more OCB ( Schmidthuber and Hilgers, 2019 ).…”
Section: Introductionmentioning
confidence: 99%